(untitled) (Journal of the College of Basic Education, 2026)
Arabic Poetry has long occupied a prominent position in recording human experience and expressing the transformations of the human soul through different historical periods. It has served as a vivid register of emotional states, reflecting the fluctuating interplay between joy and sorrow, and revealing the inner dimensions of the poet’s self in its interaction with psychological and social reality. The quality of poetic production is largely determined by the depth of artistic vision, the refinement of style, and the poet’s ability to penetrate the essence of human experience and convey it in a manner that resonates with the recipient, the more profound, authentic, and innovative the poetic expression becomes. The true poet transcends the limits of personal experience to reach broader human horizons, transforming poetry into a sincere mirror of emotions and a precise expression of conflicting feelings, whether in moments of delight or in times of pain and suffering. In this context, appropriate occasions constitute a fertile space for stimulating the poet’s sensitivity and enabling the release of intense emotion, provided that the poetic experience is grounded in sincerity of feeling and expressive power, free from artificiality and exaggeration. Ibn al-Rumi stands out as one of the most prominent Abbasid poets whose poetry clearly embodies the duality of joy and sorrow. His poetic discourse demonstrates a remarkable capacity to depict psychological emotions in their various contexts, whether in moments of happiness or in situations of loss and grief. Accordingly, this study examines selected poems by Ibn al-Rumi through two main axes: the first explores the manifestations of joy in his poetry, while the second investigates the features of sorrow and grief within his poetic experience, highlighting their artistic and emotional dimensions.